The Ornithological Collection of the Agricultural Sciences Museum housed in the Bourbon Palace of Portici (Italy) - Fraissinet, Maurizio; Labriola, Claudio (BORNH Bulletin of Regional Natural History, 2021)
The ornithological collection of the Agricultural Sciences Museum, hosted at the Department of Agricultural Sciences at the Bourbon Palace of Portici, was started in 1889. In 1920, under the direction of Filippo Silvestri, there was a notable increase in the number of specimens. This increase continued in the following years, until the collection reached around 400 specimens in 1976. In the same year, Professors Domenico Scaramella and Luigi Filippo Russo published the first and, until now, only complete analysis of the single specimens, classifying them with the systematic criteria of the time. After 45 years, the Agricultural Sciences Museum Direction felt it was appropriate to review the status of the collection, both to ascertain the presence of the specimens mentioned in previous works, and to verify the preservation status of such specimens. A species check-list was compiled, of the 437 specimens found, belonging to 271 species, 70 families, and 25 orders. It is worth noting the presence of some extinct species - Moloka’i Creeper (Paroreomyza flammea) and Leysan Rail (Zapornia palmeri) – and probably extinct species: Ou (Psittirostra psittacea) and Slender–billed Curlew (Numenius tenuirostris).